Synthesis, antimicrobial and antiproliferative properties of epi-oligomycin A, the (33S)-diastereomer of oligomycin A. Issue 21 (1st November 2020) - Lysenkova, Lyudmila N.; Saveljev, Oleg Y.; Omelchuk, Olga A.; Zatonsky, George V.; Korolev, Alexander M.; Grammatikova, Natalya E.; Bekker, Olga B.; Danilenko, Valery N.; Dezhenkova, Lyubov G.; Mavletova, Dilara A.; Scherbakov, Alexander M.; Shchekotikhin, Andrey E.
Abstract: We describe the synthesis of epi-oligomycin A, a (33 S )-diastereomer of the antibiotic oligomycin A. The structure of (33 S )-oligomycin A was determined by elemental analysis, spectroscopic studies, including 1D and 2D NMR spectroscopy, and mass spectrometry. Isomerization of C33 hydroxyl group led to minor changes in the potency against Aspergillus niger, Candida spp., and filamentous fungi whereas the activity against Streptomyces fradiae decreased by approximately 20-fold compared to oligomycin A. We observed that 33-epi-oligomycin A had the same activity on the human leukemia cell line K562 as oligomycin A but was more potent for the multidrug resistant subline K562/4. Non-malignant cells were less sensitive to both oligomycin isomers. Finally, our results pointed at the dependence of the cytotoxicity of oligomycins on oxygen supply. Graphical Abstract: